Drug metabolite identification using ultrahigh‐performance liquid chromatography–ultraviolet spectroscopy and parallelized scans on a tribrid Orbitrap mass spectrometer. (9th March 2020) - Wilkinson, Stephen D.; Martin, Scott; Orton, Alexandra L.; Markandu, Roshini; Jones, Barry C.
Abstract : Rationale: To capture all metabolites in metabolite identification studies, MS/MS information is required in both positive and negative ionization mode, usually involving several sample injections to gain all information about samples. A high‐resolution and high mass accuracy quadrupole/linear trap/Orbitrap tribrid instrument was used to gain this information in a novel single injection 'capture‐all' approach to metabolite identification. Methods: Diclofenac, a model compound, was incubated in human and rat hepatocytes. These incubated samples were run using an ultrahigh‐performance liquid chromatography/ultraviolet (UHPLC–UV) system coupled to a Thermo Fusion tribrid mass spectrometer. Five parallel scans were used: positive and negative ion full scan, data‐dependent MS/MS, both high energy dissociation and collision‐induced dissociation, and data‐independent all ion fragmentation (AIF) spectra were collected in positive and negative ion mode. Results: Nine metabolites were identified; a metabolite observed in the UV trace, but not positive ion full scan MS, was detected in the same sample injection by negative ion full scan MS. This was identified as a sulphate metabolite, and the corresponding negative ion AIF allowed for some structural elucidation. The use of a photo‐diode array (PDA) detector allowed for spectral assessment in case of changes in absorbance spectra, and the subsequent semi‐quantification of metabolites. Conclusions: This method provided good‐quality MS/MS data across the m / z range in both positive and negative ion mode. The addition of both negative ion full scan MS and negative ion MS/MS allowed for the detection and structural elucidation of metabolites not observed in positive ion mode. The use of the PDA detector allowed for the semi‐quantification of metabolites.